Analisis Struktur Organisasi Markas Besar Kepolisian Negara Republik Indonesia: Kompleksitas, Sentralisasi dan Formalisasi - Mukhtas, Haryadi; Sutiyo, Sutiyo (Jurnal Keamanan Nasional, 2019)
This study evaluates the organizational structure of the Indonesian Police by analyzing the complexity, centralization, and formalization of the organization. The design of this study is qualitative descriptive, and data are collected through in-depth interviews, observations, and documentary study. The results of this study present that the restructuring of the Indonesian Police through Perkapolri No. 6 tahun 2017 has enlarged the structure of headquarters and increased the complexity, centralization, and formalization of the organization. The structure makes the Police a mechanical organization, which is not suitable for the dynamics of society. The restructuring should make efficient the headquarters and strengthen the local offices so that the Police become an organic structure more responsive to the changes. Theoretically, structural dimensions are not always sufficient to analyze organizational issues. They should be improved by adding a process dimension of the organization that includes the alignment of all divisions and compliance with the organization.